2017
DOI: 10.1002/lt.24984
|View full text |Cite
|
Sign up to set email alerts
|

Longterm calcineurin inhibitor therapy and brain function in patients after liver transplantation

Abstract: Calcineurin inhibitors (CNIs) frequently induce neurological complications early after orthotopic liver transplantation (OLT). We hypothesize that longterm CNI therapy after OLT causes dose-dependent cognitive dysfunction and alteration of brain structure. In this study, 85 OLT patients (20 with CNI-free, 35 with CNI low-dose, and 30 with standard-dose CNI immunosuppression) underwent psychometric testing and cerebral magnetic resonance imaging approximately 10 years after OLT to assess brain function and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 33 publications
4
65
0
1
Order By: Relevance
“…To analyse the discussed underlying mechanism of CNI‐induced neurotoxicity we performed a single centre observational study in patients who had undergone liver transplantation 10 years before to investigate CNI‐related alterations in cognitive function, brain structure and metabolism, by using combined psychometric testing, magnetic resonance imaging and magnetic resonance spectroscopy (MRS). The results concerning cognitive dysfunction and alterations of brain structure in CNI‐treated patients have been reported previously . This sub‐study concentrates on the question whether the observed cognitive alterations are related to or accompanied by metabolic alterations of the brain measured with phosphorus and proton MRS.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…To analyse the discussed underlying mechanism of CNI‐induced neurotoxicity we performed a single centre observational study in patients who had undergone liver transplantation 10 years before to investigate CNI‐related alterations in cognitive function, brain structure and metabolism, by using combined psychometric testing, magnetic resonance imaging and magnetic resonance spectroscopy (MRS). The results concerning cognitive dysfunction and alterations of brain structure in CNI‐treated patients have been reported previously . This sub‐study concentrates on the question whether the observed cognitive alterations are related to or accompanied by metabolic alterations of the brain measured with phosphorus and proton MRS.…”
Section: Introductionmentioning
confidence: 67%
“…The subjects were recruited as previously described in detail . To sum up, all patients treated at the liver transplantation outpatient clinic at Hannover Medical School, who had had liver transplantation more than 2 years before and had the inclusion criteria of age ≥18 years at the time of transplantation and who also had a stable immunosuppressive therapy for at least 2 years, were asked to participate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations